FINANCIAL MANAGEMENT AND ITS INFLUENCE ON THE CREDIT RECOVERY OF THE SAVINGS AND CREDIT COOPERATIVE CHAMBER OF COMMERCE OF ECUADOR - Vera Zambrano, José (2025)
This study evaluates the influence of financial management on the credit recovery of the Savings and Credit Cooperative “Cámara de Comercio del cantón Bolívar Ltda.” during the years 2021–2023. The research is descriptive and non-experimental in nature and employed a quantitative approach to analyze financial indicators such as liquidity, indebtedness, and profitability. Additionally, a survey validated through the Delphi method was conducted with a population of 8 employees from the credit and collections department. The results revealed a moderate positive correlation between financial management and credit recovery. Although financial indicators show stability, there are still aspects that require improvement, such as the increasing delinquency rate and the lack of member awareness regarding credit policies. In conclusion, the cooperative’s financial management demonstrates strengths in its liquidity and profitability levels, while emphasizing that credit recovery requires stricter strategies and effective communication with members to ensure long-term sustainability. Keywords: financial management; credit recovery; cooperatives.